Radical carbonylations using a continuous microflow system - Fukuyama, Takahide; Rahman, Md. Taifur; Kamata, Naoya; Ryu, Ilhyong (Beilstein Journal of Organic Chemistry, 2009)
Radical-based carbonylation reactions of alkyl halides were conducted in a microflow reactor under pressurized carbon monoxide gas. Good to excellent yields of carbonylated products were obtained via radical formylation, carbonylative cyclization and three-component coupling reactions, using tributyltin hydride or TTMSS as a radical mediator.
Keywords: continuous flow system; microreactor; radical carbonylation; radical mediator; V-65

Microreactors in Organic Synthesis and Catalysis - Wirth, T. (Wiley-VCH, 2008)

Micro Process Engineering - Hessel, V.; Renken, A.; Schouten, J. C.; Yoshida, J. (Wiley-VCH, 2009)

(untitled) - Jas, G.; Kirschning, A. (Chem.–Eur. J., 2003)

(untitled) - Fukuyama, T.; Rahman, M. T.; Sato, M.; Ryu, I. (Synlett, 2008)

(untitled) - Fukuyama, T.; Shinmen, M.; Nishitani, S.; Sato, M.; Ryu, I. (Org. Lett., 2002)

(untitled) - Sugimoto, A.; Fukuyama, T.; Sumino, Y.; Takagi, M.; Ryu, I. (Tetrahedron, 2009)

(untitled) - Usutani, H.; Tomida, Y.; Nagaki, A.; Okamoto, H.; Nokami, T.; Yoshida, J. (J. Am. Chem. Soc., 2007)

(untitled) - Sahoo, R. H.; Kralj, J. G.; Jensen, K. F. (Angew. Chem., Int. Ed., 2007)

(untitled) - Tanaka, K.; Motomatsu, S.; Koyama, K.; Tanaka, S.; Fukase, K. (Org. Lett., 2007)

(untitled) - Carrel, F. R.; Geyer, K.; Codée, J. D. C.; Seeberger, P. H. (Org. Lett., 2007)

(untitled) - Bogdan, A. R.; Mason, B. P.; Sylvester, K. T.; McQuade, D. T. (Angew. Chem., Int. Ed., 2007)

(untitled) - Fukuyama, T.; Kobayashi, M.; Rahman, M. T.; Kamata, N.; Ryu, I. (Org. Lett., 2008)

(untitled) - Odedra, A.; Geyer, K.; Gustafsson, T.; Gilmou, R.; Seeberger, P. H. (Chem. Commun., 2008)

(untitled) - Ryu, I. (Chem. Soc. Rev., 2001)

(untitled) - Ryu, I.; Chatgilialoglu, C.; Crich, D.; Komatsu, M. (Chem. Rev., 1999)

(untitled) - Ryu, I.; Sonoda, N. (Angew. Chem., Int. Ed., 1996)

(untitled) - Ryu, I.; Sonoda, N.; Curran, D. P. (Chem. Rev., 1996)

(untitled) - Rahman, M. T.; Fukuyama, T.; Kamata, N.; Sato, M.; Ryu, I. (Chem. Commun., 2006)

(untitled) - Miller, P. W.; Long, N. J.; de Mello, A. J.; Vilar, R.; Gee, A.; Passchier, J. (Chem. Commun., 2006)

(untitled) - Murphy, E. R.; Martinelli, J. R.; Zaborenko, N.; Buchwald, S. L.; Jensen, K. F. (Angew. Chem., Int. Ed., 2007)

(untitled) - Ryu, I.; Kusano, K.; Ogawa, A.; Kambe, N.; Sonoda, N. (J. Am. Chem. Soc., 1990)

(untitled) - Ryu, I.; Miyazato, H.; Kuriyama, H.; Matsu, K.; Tojino, M.; Fukuyama, T.; Minakata, S.; Komatsu, M. (J. Am. Chem. Soc., 2003)

(untitled) - Tojino, M.; Otsuka, N.; Fukuyama, T.; Matsubara, H.; Schiesser, C. H.; Kuriyama, H.; Miyazato, H.; Minakata, S.; Komatsu, M.; Ryu, I. (Org. Biomol. Chem., 2003)

(untitled) - Ryu, I.; Kusano, K.; Yamazaki, H.; Sonoda, N. (J. Org. Chem., 1991)

Organosilanes in Radical Chemistry - Chatgilialoglu, C. (John Wiley & Sons Ltd., 2004)

(untitled) - Ryu, I.; Hasegawa, M.; Kurihara, A.; Ogawa, A.; Tsunoi, S.; Sonoda, A. (Synlett, 1993)

(untitled) - Kishimoto, Y.; Ikariya, T. (J. Org. Chem., 2000)